2011
DOI: 10.1136/adc.2009.180596
|View full text |Cite
|
Sign up to set email alerts
|

Antibody persistence following MeNZB vaccination of adults and children and response to a fourth dose in toddlers

Abstract: Immune response to MeNZB was most sustained in adults. In infants, bactericidal titres decayed almost to baseline by 7 months after dose 3. Toddlers showed marked immune response following a fourth dose suggesting memory. Persisting antibody is likely to be necessary for ongoing protection, as seen with serogroup C meningococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Following three doses of the monovalent MenB OMV vaccine (MeNZB) used to help control a clonal outbreak in New Zealand: only 74% of 6-8 month-old [27], 75% of 16-24 month-old [28] and 74-79% of 8-12 year-old children [29] developed a seroresponse, as assessed at 4 weeks after dose 3 (four-fold rise in hSBA titer compared to baseline). Age-dependent antibody decline against this PorA vaccine antigen was also described; 7 months following the third dose of MeNZB in 6-8 month-old infants only 28% had persistent hSBA ≥4; compared to 36%, 14 months following the third dose in 8-12 year-old children; and 50%, 10 months following the third dose in adults [30]. Accordingly, as the rate of decline of hSBA titers (or waning of antibody) is differential according to age and strain, it is possible that susceptibility to meningococcal infection and duration of vaccine protection might be differential according to age and geographical region (depending on the expression of proteins in the circulating disease-causing strains).…”
Section: Discussionmentioning
confidence: 93%
“…Following three doses of the monovalent MenB OMV vaccine (MeNZB) used to help control a clonal outbreak in New Zealand: only 74% of 6-8 month-old [27], 75% of 16-24 month-old [28] and 74-79% of 8-12 year-old children [29] developed a seroresponse, as assessed at 4 weeks after dose 3 (four-fold rise in hSBA titer compared to baseline). Age-dependent antibody decline against this PorA vaccine antigen was also described; 7 months following the third dose of MeNZB in 6-8 month-old infants only 28% had persistent hSBA ≥4; compared to 36%, 14 months following the third dose in 8-12 year-old children; and 50%, 10 months following the third dose in adults [30]. Accordingly, as the rate of decline of hSBA titers (or waning of antibody) is differential according to age and strain, it is possible that susceptibility to meningococcal infection and duration of vaccine protection might be differential according to age and geographical region (depending on the expression of proteins in the circulating disease-causing strains).…”
Section: Discussionmentioning
confidence: 93%
“…During pre-licensure trials, fever (≥38°) was reported in approximately 16-37% of doses in the early infant study, 15% of doses given during late infant and toddler studies, and 0-3% of 8-12-year old children and adults [36,45,46,53,54]. Self-limited systemic reactions were common, including arthragia in 6% of 8-12 year old children.…”
Section: Previous Experience With Outer Membrane Vesicle Vaccinesmentioning
confidence: 98%
“…Experience with other meningococcal vaccines has shown that waning of bactericidal antibody titres was associated with a decline in vaccine effectiveness following infant vaccination with serogroup C meningococcal conjugate vaccines, 12 adolescent vaccination with an investigational outer membrane vesicle vaccine in Norway 13 and infant vaccination with the New Zealand outer membrane vesicle vaccine. 10,14 Predicting the potential impact of a decline in bactericidal antibodies on vaccine effectiveness following vaccination with 4CMenB is less straightforward. The serogroup C meningococcal conjugate and outer membrane vesicle vaccines generate an immune response primarily directed against a single antigen (the capsular polysaccharide and PorA, respectively), whereas 4CMenB is a multicomponent vaccine that aims to induce antibodies against each component.…”
Section: Discussionmentioning
confidence: 99%